2013
DOI: 10.1021/mp400116q
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics, Physical Stability and Solubility Advantage from Amorphous Indapamide Drug

Abstract: This study for the first time investigates physicochemical properties of amorphous indapamide drug (IND), which is a known diuretic agent commonly used in the treatment of hypertension. The solid-state properties of the vitrified, cryomilled and ball-milled IND samples were analyzed using X-ray powder diffraction (XRD), mass spectrometry, nuclear magnetic resonance (NMR), infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC) and broadband dielectric spectroscopy (BDS). These analytical techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 64 publications
5
58
0
Order By: Relevance
“…Thus, the life expectancy of the amorphous state has to be addressed and optimized to secure protocols of formulation (Bhugra and Pikal, 2008). In recent years, a great effort has been dedicated to the study of "crystal to glass transformation" induced by milling (Wojnarowska et al, 2013) (Descamps et al, 2015). To date, a streamlining of transformations reached by milling has not been attained even if some empirical rules are emerging from current investigations (Dujardin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the life expectancy of the amorphous state has to be addressed and optimized to secure protocols of formulation (Bhugra and Pikal, 2008). In recent years, a great effort has been dedicated to the study of "crystal to glass transformation" induced by milling (Wojnarowska et al, 2013) (Descamps et al, 2015). To date, a streamlining of transformations reached by milling has not been attained even if some empirical rules are emerging from current investigations (Dujardin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect to consider when milling crystalline materials is the fact that, the amorphous phase inevitably contains some quantity of moisture (either generated from within the material in case of crystalline hydrates or adsorbed from the environment). A recent study on ball milled indapamide (Wojnarowska et al, 2013) has suggested the presence of a water relaxation peak rather than the typical relaxation processes of amorphous phase. The distribution of this water affects the molecular dynamics of the amorphous phase and is therefore important in defining the stability of this phase.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7][8] Moreover, the carbohydrazide small molecule function as an essential pharmacophore in many therapeutically valuable materials, for example, the antiviral, antibacterial and antitubercular biological activities were dramatically increased by inserting the thiophene-carbohydrazide in the structure of big molecules. [5][6][7][8][9][10][11][12] Therefore, a huge number of heterocyclic carbohydrazide derivatives have been made available. [6][7][8][9][10][11][12][13][14][15] The prototropic tautomers are compounds that can be interconverted from molecule to another via single proton migration from group to the close neighbor atom.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Therefore, a huge number of heterocyclic carbohydrazide derivatives have been made available. [6][7][8][9][10][11][12][13][14][15] The prototropic tautomers are compounds that can be interconverted from molecule to another via single proton migration from group to the close neighbor atom. 16 It's known that there is no pure separating line between such tautomers and isomers: tautomer is obviously isomer that transform with a comparatively depressed activation energy <20 kcal mol À1 .…”
Section: Introductionmentioning
confidence: 99%